The chronicles of Narnia, Prince Caspian : the movie storybook - Jacobs, Lana.; Adamson, Andrew; Lewis, C. S. (Clive Staples), 1898-1963.; Markus, Christopher; McFeely, Stephen; Walden Media; Walt Disney Enterprises (London: : Harper Collins Children's Books, 2008)
A movie storybook about the four Pevensie children who return to Narnia to help Prince Caspian defeat the Telmarines and restore the kingdom.
"Based on the book by C.S. Lewis."
"Based on the new movie!"--Cover.
"Based on the screenplay by Andrew Adamson & Christopher Markus & Stephen McFeely."
Spine title: Prince Caspian.
4.8
3-6.
Keywords: Good and evil -- Juvenile fiction; Magic -- Juvenile fiction; Narnia (Imaginary place) -- Juvenile fiction; Princes -- Juvenile fiction; Fantasy; Good and evil -- Fiction; Magic -- Fiction; Narnia (Imaginary place) -- Fiction; Princes -- Fiction; Good and evil -- Fiction; Magic -- Fiction; Movie novels; Narnia (Imaginary place) -- Fiction; Princes -- Fiction; Fantastic fiction; Fantastic fiction; Movie novels